PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PENGEMBANGAN ORGANISASI MUSEUM NEGERI NUSA TENGGARA BARAT (NTB) DALAM ERA TRANSFORMASI DIGITAL - Istiana, Diana; Muttaqillah Muttaqillah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of transformational leadership and human resource quality on the organizational development of the in the Digital Transformation Era. The type of research employed is causal-associative research, and data collection was conducted using a census method. The population in this study consists of employees of the NTB State Museum, totaling 50 employees. Data analysis was performed using Multiple Linear Regression with IBM SPSS version 26. The results of the study indicate that: (1) Transformational Leadership has a positive and significant effect on the Organizational Development of the NTB State Museum, (2) Human Resource Quality has a positive and significant effect on the Organizational Development of the NTB State Museum.